Parents’ wellbeing: perceptions of happiness and challenges in parenthood in Latin America - Angel Urbina-Garcia (International Journal of Qualitative Studies on Health & Well-Being)
Introduction Traditional research on parenthood and wellbeing often employs a positivist perspective and focuses on non-LA samples -limiting our knowledge and understanding of the influence of cultural components such as Machismo and Marianismo, have in parents’ wellbeing. This study explored how Latin American (LA) parents’ wellbeing is influenced by parenthood in a culture strongly influenced by such gender-based perspectives. Methods An interpretative perspective was employed to qualitatively explore fifteen LA parents’ lived experiences and data were analysed via Thematic Analysis. The American Psychological Association’s Journal Article Reporting Standards for Qualitative Research (JARS-Qual), was followed to compile this paper. Results Results showed that socio-economic factors such as crime, violence, and economic inequality, negatively influence parents’ wellbeing -emotions experienced and life satisfaction. Discussion Parents find joy in sharing own personal experiences with their children and passing on gender-based models. However, parents perceive family pressure as a “burden” when expected to follow principles of Machismo/Marianismo. Similar to Asian, but unlike European parents, LA parents experience a mixture of positive and negative emotions whilst parenting -shaped by Machismo and Marianismo. This study makes a unique contribution by uncovering the unique influence of LA socio-economic challenges and cultural impositions and expectations and its influence on parental wellbeing.